Meta-Analysis of Relationship of Sleep Quality and Duration With Risk of Diabetic Retinopathy - Zheng, Zhenzhen; Wang, Chaoyu; Li, Chunhe; Wu, Qinglan; Chen, Xiaojuan; Chen, Huimin; Liao, Huizhao; Zhu, Jinru; Lin, Junyan; Ou, Xudong; Zou, Zhihong; Liang, Jinhua; et al. (Frontiers in Endocrinology, 2022)
Objective: A meta-analysis is used to explore the relationship of sleep quality and duration with the risk of diabetic retinopathy (DR). Method: Cochrane Library, PubMed, Embase, and other databases are searched from their establishment to April 2022. Literature on the relationship of sleep quality and duration with DR risk published in various databases is collected, and two researchers independently screen the literature, extract data, and evaluate the quality of the included articles. The meta-analysis is performed with R 5.4.1 software. Results: A total of 7 articles are selected, including 4,626 subjects. The results show a positive correlation between sleep quality and DR risk. When comparing the sleep quality scores of "DR" (experimental group) and "NO DR" (control group), the Pittsburgh sleep quality index(PSQI) score of the DR group is significantly higher than that of the NO DR group (MD = 2.85; 95% confidence interval [CI] 1.92, 3.78), while the ESS score of the DR group is also significantly higher than that of the NO DR group (MD = 1.17; 95% confidence interval [CI] 0.14 to 2.30), so the sleep quality score of the DR group is higher than that of the NO DR group in both the PSQI and ESS scores, which confirms that low sleep quality is a risk factor for DR. Long sleep duration is also associated with the risk of developing DR; the number of adverse events (DR prevalence) is higher for “long sleep duration” than “normal sleep duration” [OR = 1.83, 95%CI 1.36–2.47, P < 0.0001], suggesting that long sleep duration can cause increased DR risk. Short sleep duration is also associated with the occurrence of DR [OR = 1.49, 95%CI 1.15–1.94), P = 0.003] and can increase DR risk. Conclusion: Sleep quality and duration (including long and short sleep duration) are significantly associated with DR. To reduce DR risk, sleep intervention should be actively carried out, lifestyle changes should be made, and attention should be paid to the role of DR management.